Effect of sugar reduction and addition of corn fibre and polydextrose on pore size and syneresis of yoghurt. (June 2022) - Gomes, Elisângela Ramieres; Carneiro, Lauren Carvalho Montalvão; Stephani, Rodrigo; Carvalho, Antônio Fernandes de; Renhe, Isis Rodrigues Toledo; Wolfschoon-Pombo, Alan F.; Perrone, Ítalo Tuler
Abstract: This study investigated the effect of sugar reduction and replacement by corn fibre and polydextrose on yoghurt gel pore size and syneresis. Five yoghurt formulations were produced with 9, 4.5 and 0% sucrose, and also 4.5% with added 2% corn fibre or polydextrose. The increasing demand for sugar reduction in dairy products justifies studies on new formulations such as fibre addition. Sucrose reduction from 9% to 0% led to a decrease in average matrix pore size and increased syneresis. Fibre or polydextrose addition effectively reduced syneresis, despite bigger matrix pore sizes. Fermentation profile, acidity and pH values were not significantly affected by compositional changes.